The entrepreneurship in the students of the unmsm and its relation with some variables sociodemografic - Loli Pineda, Alejandro (2009)
This study has as an objective to know the entrepreneurship attitude of Universidad Nacional Mayor de San Marcos students and their relationship to some demographic variables, which have been taken from a sample of 182 students belonging to different engineering specialties and from third to the fifth year of studies. The results indicate that the majority of the students have a positive attitude towards the creativity and entrepreneurship, in the same way, there is a significative and positive correlation between their components. With respect the demographics and psychosocial variables, there is a difference significative according to the age groups, year of study, development of entrepreneurship, College and Academic Department, and kind of entrepreneurship activity, it could say, the presence of those variables allow to infer that there are differences respect some creativity and entrepreneurship factors.